32nd International Symposium on Computer Architecture (ISCA'05)
DOI: 10.1109/isca.2005.32
|View full text |Cite
|
Sign up to set email alerts
|

Improving Program Efficiency by Packing Instructions into Registers

Abstract: New processors, both embedded and general purpose, often have conflicting design requirements involving space, power, and performance. Architectural features and compiler optimizations often target one or more design goals at the expense of the others. This paper presents a novel architectural and compiler approach to simultaneously reduce power requirements, decrease code size, and improve performance by integrating an instruction register file (IRF) into the architecture. Frequently occurring instructions ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(50 citation statements)
references
References 17 publications
0
50
0
Order By: Relevance
“…al. [12] present a technique for reducing program size, power consumption and execution time by storing commonly used instructions in an instruction register file. They allow instructions to reference multiple entries in the instruction register file.…”
Section: Compilationmentioning
confidence: 99%
“…al. [12] present a technique for reducing program size, power consumption and execution time by storing commonly used instructions in an instruction register file. They allow instructions to reference multiple entries in the instruction register file.…”
Section: Compilationmentioning
confidence: 99%
“…However, in the memory format instructions, the displacement field has to be shortened and uses encoded into the new free space. Although this implementation is specific to the Alpha, other researchers have found that free bits are common in other ISAs, such as MIPS [Hines et al 2005].…”
Section: Isa Impactmentioning
confidence: 99%
“…Our initial strategy for selecting instructions to reside in the IRF was to simply choose the most frequently accessed instructions [1]. We now distinguish instructions by howm anyo ft he fiveR ISA slots are consumed.…”
Section: Progress and Outcomesmentioning
confidence: 99%
“…While a compiler optimization and/or an architectural feature may be developed to improve one design goal of a processor,i to ften comes at the detriment of another.A n instruction register file (IRF), unlikemost architectural and compiler enhancements, has been shown to simultaneously reduce power requirements, decrease code size, and improve performance [1]. This paper describes the progress and outcomes of the NSF Grant CNS-0615085, whose main goal is to enhance the effectiveness of utilizing an IRF.W ea lso introduce a tagless hit instruction cache (IC) that reduces energy consumption without increasing execution time by guaranteeing hits in this small IC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation